Legal Regulation of Health Restrictions and Current Law Enforcement Practices in the Organization of Training - Neustroev, Sergey Sergeevich; Arinushkina, Anna Alexandrovna; Bakhtin, Maksim Borisovich; Dovbysh, Svetlana Evgenevna; Molchanova, Valeriya Sergeevna; Shikhnabieva, Tamara Shikhgasanovna (Journal of History Culture and Art Research, 2018)
The article provides an overview of the legislation of the Russian Federation regulating special features of education for persons with disabilities. The focus is on both national and local legislative acts, regulating health restrictions in education. First, we review the legislation on special conditions created for students with limited health opportunities in educational organizations. Second, we conduct a thematic review of court decisions on ensuring the rights of persons with limited health opportunities to receive education. The article also presents results of our analysis and reviews the current law enforcement practice on ensuring the rights of persons with disabilities on education, as well as considers additional rights and measures of social support for persons with disabilities in connection with their participation in educational relations. In addition, we analyze and generalize new trends in legal regulation on the implementation of educational activities according with adapted educational programs for the students with disabilities. The article concludes with the following statements: (a) a systemic analysis of the legislation can be used with the aim of improving the implementation of the adapted educational programs; (b) the legislation can be improved via special proposals that determine the features of education for children with limited health opportunities.